2014
DOI: 10.1371/journal.pone.0108855
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Attenuates Ischemia-Reperfusion-Induced Apoptosis and Autophagy in Mouse Liver via Regulation of the ROS/JNK/Bcl-2 Pathway

Abstract: BackgroundHepatic ischemia–reperfusion injury (HIRI) remains a pivotal clinical problem after hemorrhagic shock, transplantation, and some types of toxic hepatic injury. Apoptosis and autophagy play important roles in cell death during HIRI. It is also known that N-acetylcysteine (NAC) has significant pharmacologic effects on HIRI including elimination of reactive oxygen species (ROS) and attenuation of hepatic apoptosis. However, the effects of NAC on HIRI-induced autophagy have not been reported. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 41 publications
5
63
0
4
Order By: Relevance
“…[71][72][73][74] Recently, NAC was reported to attenuate ischemia-reperfusion-induced autophagy via ROS/JNK/bcl-2 pathway. 75 Therefore, we speculated that ROS-mediated MAPK/Bcl-2 may be a novel mechanism in the protective effects of NAC on SiNPs-induced autophagy in endothelial cells. Studies revealed that mTOR inhibition could lead to and even promote apoptosis, 76,77 suggesting that the detected downregulation of mTOR may also be responsible for SiNPs-induced apoptosis.…”
mentioning
confidence: 99%
“…[71][72][73][74] Recently, NAC was reported to attenuate ischemia-reperfusion-induced autophagy via ROS/JNK/bcl-2 pathway. 75 Therefore, we speculated that ROS-mediated MAPK/Bcl-2 may be a novel mechanism in the protective effects of NAC on SiNPs-induced autophagy in endothelial cells. Studies revealed that mTOR inhibition could lead to and even promote apoptosis, 76,77 suggesting that the detected downregulation of mTOR may also be responsible for SiNPs-induced apoptosis.…”
mentioning
confidence: 99%
“…17,18 A previous study by Wang and associates showed that NAC can prevent hepatic IRI-induced autophagy and apoptosis by influencing the Janus kinase signaling pathway. 19 The effect of NAC on suppressing the TLR4/IRF5 axis and its downstream proinflammatory cytokines suggests another possible mechanism of action for preventing hepatic IRI. Findings from our present study show that activation of the TLR4/IRF5 signaling axis may have an essential role in the early inflammatory phase of hepatic IRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism still remains unclear. Mounting evidence indicates that apoptosis results in post-ischemic cardiomyocyte death [26] . In a previous study, SFN could protect cardiomyocytes against oxidative damage [27] .…”
Section: Discussionmentioning
confidence: 99%